1990
DOI: 10.2135/cropsci1990.0011183x003000050016x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity for Restriction Fragment Length Polymorphisms: Relation to Estimated Genetic Effects in Maize Inbreds

Abstract: Restriction fragment length polymorphisms (RFLPs) have been proposed for investigating relationships among inbred lines and predicting heterosis and performance of single-cross hybrids in maize (Zea mays L.). Such use was evaluated in 20 maize inbreds classified as first-cycle, second-cycle, good, and poor lines, and in diallel crosses within types. Eight generations (parents, F 1 , F 2 , F 3 , backcrosses, and backcrosses selfed) from 67 crosses were evaluated for grain yield in five Iowa environments. Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
2
7

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 0 publications
9
78
2
7
Order By: Relevance
“…Thus authors reiterated that significant difference between the above studies may be used for prediction of heterosis in the silkworm breeding programme similar to the reports of plant breeding programmes [12,16,17] . The optimum level of genetic distance is necessary to obtain heterosis.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus authors reiterated that significant difference between the above studies may be used for prediction of heterosis in the silkworm breeding programme similar to the reports of plant breeding programmes [12,16,17] . The optimum level of genetic distance is necessary to obtain heterosis.…”
Section: Resultsmentioning
confidence: 66%
“…D 2 statistic by Mahalanobis [14] has been extensively used in predicting the hybrid performance on the basis of morphological traits. However, these methods require extensive field tests and crossing and hence, a need is now felt to determine genetic distance at the molecular level and thus to predict hybrid performance [16] . Small populations are particularly vulnerable to inbreeding and loss of genetic diversity through genetic drift [25] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Messmer et al it is difficult to classify varieties as types being potentially valuable in hybrid development by geographic origin or endosperm type alone, because many varieties were mixed in origin, or were introgressed between each other [38]. In addition, pedigree relationships revealed by DNA markers could only predict the heterosis of hybrids developed by parents with certain levels of differentiation [36][37][38][39][40]. The given hierarchical classification reveals the differentiation at different levels (ecotypes and eco-geographical types) within indica, and may provide a framework to test heterosis at different levels.…”
Section: Potential Utilization Of Ecotypyes and Eco-geographical Typementioning
confidence: 99%
“…Betrán et al (2003) suggested that heterosis can be better predicted only when GD is smaller than a certain threshold. Moreover, studies have suggested that the correlation is dependent on the investigated germplasm and GD calculation methods (Melchinger et al 1990;Tams et al 2006). …”
Section: Introductionmentioning
confidence: 99%